2020
DOI: 10.1093/jee/toaa181
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Bark and Ambrosia Beetle (Coleoptera: Curculionidae) Catches in Trapping Surveys for Longhorn and Jewel Beetles

Abstract: Bark and ambrosia beetles are commonly moved among continents within timber and fresh wood-packaging materials. Routine visual inspections of imported commodities are often complemented with baited traps set up in natural areas surrounding entry points. Given that these activities can be expensive, trapping protocols that attract multiple species simultaneously are needed. Here we investigated whether trapping protocols commonly used to detect longhorn beetles (Coleoptera: Cerambycidae) and jewel beetles (Cole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 71 publications
1
23
1
Order By: Relevance
“…Ethanol-baited traps are the predominant method for monitoring ambrosia beetle populations, including Xylosandrus spp. in ornamental nurseries (Reding et al, 2010(Reding et al, , 2011(Reding et al, , 2015, forests (Hauptman et al 2019;Martínez et al 2019;Marchioro et al 2020), and urban landscapes and parks (Klingeman et al 2017;Gugliuzzo et al 2019a). Several types of traps are commercially available, and homemade inexpensive bottle traps can be easily made and baited with lures (Egonyu and Torto 2018;Owens et al 2019b).…”
Section: Trapsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethanol-baited traps are the predominant method for monitoring ambrosia beetle populations, including Xylosandrus spp. in ornamental nurseries (Reding et al, 2010(Reding et al, , 2011(Reding et al, , 2015, forests (Hauptman et al 2019;Martínez et al 2019;Marchioro et al 2020), and urban landscapes and parks (Klingeman et al 2017;Gugliuzzo et al 2019a). Several types of traps are commercially available, and homemade inexpensive bottle traps can be easily made and baited with lures (Egonyu and Torto 2018;Owens et al 2019b).…”
Section: Trapsmentioning
confidence: 99%
“…However, other Lindgren trap colors (e.g., green, purple) also have been used to trap other woodboring insects like emerald ash borer (Agrilus planipennis Fairmaire), and these alternative colors also will generally collect Xylosandrus spp. as long as the trap is baited with an ethanol lure (Francese et al 2013;Cavaletto et al 2020;Marchioro et al 2020). Indeed, most ethanol-baited traps have been shown suitable for monitoring the presence or absence of ambrosia beetle.…”
Section: Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we consider the number of exotic species recorded in the last few years, and especially those collected fortuitously, it is clear that current monitoring strategies are ineffective at detecting several beetle families. It is for this reason that great effort has been invested in improving monitoring strategies, survey methods, and traps [ 18 , 19 ], with a focus on the main entry points such as seaports and airports (i.e., [ 20 , 21 ]). However, much of these recent developments have targeted primarily families of forest insects, mostly wood borers, such as Curculionidae: Scolytinae and Platypodinae, Cerambycidae, and Buprestidae (e.g., [ 22 , 23 , 24 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Something that had a similar effect at a larger scale, both on endemic and invasive Mediterranean pine bark beetle species [ 9 ]. As a recent study has concluded [ 10 ], a number of trapping variables, such as trap color, lure blend, and even height should be accordingly adjusted to maximize the efficacy of a surveillance program.…”
mentioning
confidence: 99%